Faktor Pesaing Di Dalam Penilaian Permintaan Rekreasi Luar - Shuib, Ahmad (Universiti Putra Malaysia Press, 1993)
The reduction in the number of visits to a particular recreational site is influenced by the cost of travel and other socio-economic factors. For those who stay further from the particular site, the availability of alternative recreational sites along the journey will also have impacts on the visit rates. Without including the effect of the substitute sites the estimates of demand will be biased; the bias is related to misspecified errors. A demand function that does not take into account the effect of substitute sites will result in biased estimation of the benefits of outdoor recreation because the coefficient of demand will be inconsistent. A Clawson demand function is modified to include the effect of competition in the evaluation of benefits for outdoor recreation in Langkawi